Implementasi Psikotes SIM di Satpas Gresik - Muhammad Romdhonul Karim; Idha Rahayuningsih; Citrawanti Oktavia (Lembaga Pengembangan Kinerja Dosen, 2025)
Since June 2020, passing a psychological test is the main requirement to obtain and extend a driver's license, to complement the ability to concentrate, accuracy, self-control, adaptability, emotional stability and work endurance. It is expected to prevent accidents due to psychological factors from the driver. So it's not just driving and riding skills but also a driving attitude with a responsible attitude for safety. This is what soft skills are measured through the psychological test. According to the data that has been collected, many traffic accidents are caused by the psychological condition of the driver. Through psychological tests, drivers will be assessed from several aspects, namely the ability to concentrate, accuracy, self-control, adaptability, emotional stability and work endurance. And it is hoped that other drivers will also feel confident that other drivers around them have good psychological aspects so as not to endanger their safety.